DETERMINATION OF MORIN IN GREEN TEA AND COFFEE BY ADSORPTION VOLTAMMETRY USING CARBON ELECTRODES MODIFIED WITH POLY (3,4-ETHYLENEDIOXYTHIOPHENE) AND IONIC LIQUID - Peña, Daniel (2020)
This paper presents a sensitive and selective method for morin (MR) determination in the presence of rutin (RT) and quercetin (QC) on a screen-printed carbon electrode coated with poly(3,4-ethylenedioxythiophene) (PEDOT) and ionic liquids 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4), (PEDOT-BMIMBF4/SPCE). Several studies have shown that morin may be adsorbed onto the surface of the SPC electrode modified with PEDOT. Moreover, (BMIMBF4) on the surface of the modified electrode with PEDOT increased the anodic peak current nearly 52,0 % and facilitated the oxidation of morin to less positive potential values proving be an ideal surface toward the oxidation of morin. On the other hand, potential substances that may interfere with the signal of morin, such as rutin and quercetin, are oxidized to potential more and less positive respectively. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to quantify and characterize the modified electrode, pH and electrochemical parameters such as potential adsorption, adsorption time and scan rate were optimized (pH 2,7; EADS, -0,10 V; tADS, 60 s; and ʋ, 50 mVs-1). The detection limit was 0,16 μmol L-1 and the RSD was 5,2%. The usefulness of the modified electrode was used to quantify morin in green tea samples in the presence of other flavones with consistent result.